APLIKASI WEB PENGIRIMAN DAN PENERIMAAN SMS DENGAN GAMMU SMS ENGINE BERBASIS PHP - Diah Aryani; Ade Setiadi; Fifit Alfiah (CCIT Journal, 2015)
The development of the rapidly evolving technology in this era, especially in the telecommunications, media, and information (telecommunications) received positive feedback and negative in society. The technology used by the right target will be very useful in supporting the activities of either the agency or agencies. penyampaikan for information processing and information so that the information presented is fast, precise, and lack of errors, thus making the job more effectively and efficiently. Short Message Service (SMS) is the delivery of messages or information that is already being replaced by chat applications such as fuel and whatsapp. SMS has experienced growth in terms of the use and function as Polling SMS, SMS Banking, and SMS Gateway. Gammu SMS Engine Engine is used for SMS Gateway application. Gammu can be implemented in a variety of programming languages such as PHP and can be used functions as needed. Gammu SMS messaging engine is processing applications that do not perform bulk SMS delivery on most SMS gateway. The method used for Gammu SMS engines do not get hung up on a theory but a configuration setting through some source code and also through the device manager to check the port that is connected to the computer. To use the database files in a manner that is available on the database import gammu folder on the server mysql which we use to connect to the modem and mysql. To run the service engine gammu must use the command prompt by way mengetikm "gammu-smsd smsconf -i -s -c" to the process of running the engine at a command prompt first entry in the directory "bin". Knowing gammu runs aktive with the presence of link to stop and restart the service by running aktivenya gammu we can directly use gammu engine SMS to send and receive SMS..